Percorsi di macritica - DOLFI, ANNA (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2007)
This book is centred on the work of Oreste Macrí: scholar of Italian, French and Spanish literature; comparatist, metricist, theorist and translator in continual dialogue with Europe; historian and friend of the leading protagonists of the Spanish generation of '25, and in Italy a penetrating and impassioned theorist/founder of Hermeticism. With clear-sighted focus, Anna Dolfi traces the fundamental stages in his critical itinerary, especially on the Italian front, bringing out the singular mix of rigour and creative ingenuity, of philology and impassioned and ineluctable militancy, that is at the basis of an unmistakably new mode of reading the texts, of dialoguing with the authors and with the reader. In a word, what has been defined as 'Macritica', either with playful admiration or with polemical distancing by those who, alarmed by the doctrine, the creativity and the choice of canons, preferred to dwell instead on the difficulty of a language that, confirming over the years Macrì's singular hermeneutic capacity, also fully expressed his provocative nonconformism and his ironic intelligence. Accompanying the book is a precious CD-Rom, outcome of the work of a group of Anna Dolfi's young students (indicated with the initials "GRBM", that is, "Gruppo Ricercatori della Biblioteca Macrí"), which offers a complete index of the private library donated by Oreste Macrí to the "Archivio contemporaneo Bonsanti" of the Gabinetto "G. P. Vieusseux" in Florence. Open CD-ROM